Evaluación de las concentraciones de surfactantes para un fluido de perforación base aceite que mejoren la estabilidad de la emulsión (2020)
In the present work, the determination of the surfactant concentrations for an oil-based drilling fluid that improve the stability of the emulsion was carried out. For this, a sequential experimental development was carried out where six different formulations were prepared. Formulation 1 has: lime, surfactants and brine, it is used as a reference to compare the others because it has the least amount of additives, from this the others were prepared sequentially with respect to the results obtained from the formulations already prepared. Formulation 2 has: lime, surfactants, brine, and clay, was made to demonstrate the effect of clay on stability, and the addition of clay was found to improve stability in all prepared drilling fluids. Formulation 3 has: lime, surfactants, brine, clay, and calcium carbonate solids; The results showed that solids may or may not improve the stability of the emulsion depending on the amount of surfactants used to change its wettability from water to oil.